PENERAPAN PRINSIP SHARED RESPONSIBILITY SEBAGAI UPAYA DALAM PENANGGULAN KEJAHATAN TRANSNASIONAL DI KAWASAN ASIA TENGGARA - Jeanita Eka Aryanti; Handojo Leksono (Faculty of Law Universitas Sebelas Maret, 2017)
This research aims to analysis the implementation of the principle of shared responsibility as an effort to combating transnational organized crime in the Southeast Asia. The principle of Shared Responsibility examines the underexplored problem of allocation of responsibilities among multiple states and other actors. This concept in necessary given the growing number of transnational crime that occurs in Southeast Asia. The research results showed that concept of shared responsibility consist of; 1) exchange Exchange of Criminal Information and Intelligence, 2) Mutual Legal Assistance in Criminal Matters/MLA, 3)Joint Investigation, 4) Joint Operation and 5) training and technical assistance. This research also examines the efforts of the Southeast Asian Nation to combat transnational crime. This research is the normative legal research is prescriptive and applied approach to the conceptual approach, statute approach and cases approach.